2022
DOI: 10.1093/biolre/ioac213
|View full text |Cite
|
Sign up to set email alerts
|

MDSCs in pregnancy and pregnancy-related complications: an update

Abstract: Maternal-fetal immune tolerance is a process that involves complex interactions of the immune system, and myeloid-derived suppressor cells (MDSCs) have emerged as one of the novel immuno-modulator in the maintenance of maternal-fetal immune tolerance. MDSCs are myeloid progenitor cells with immunosuppressive activities on both innate and adaptive cells through various mechanisms. Emerging evidence demonstrates the accumulation of MDSCs during healthy pregnancy to establish maternal-fetal immune tolerance, plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 93 publications
0
3
0
Order By: Relevance
“…MDSCs were decreased in the peripheral blood and the endometrial tissues of patients with a history of miscarriage. 28,35 The reduction in MDSCs during a miscarriage could potentially result in decreased Treg levels, subsequently resulting in failed maternal-fetal immune tolerance. 35 Hence, changes in MDSC cells were simultaneously assessed while detecting Treg cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MDSCs were decreased in the peripheral blood and the endometrial tissues of patients with a history of miscarriage. 28,35 The reduction in MDSCs during a miscarriage could potentially result in decreased Treg levels, subsequently resulting in failed maternal-fetal immune tolerance. 35 Hence, changes in MDSC cells were simultaneously assessed while detecting Treg cells.…”
Section: Discussionmentioning
confidence: 99%
“…25 Myeloid-derived suppressor cells (MDSCs), also known as CD11b + Gr-1 + cells, 26 are an important group of immunosuppressive cells at the maternal-fetal interface, 27 which are involved in maternal-fetal immune tolerance, placental development, and fetal growth during pregnancy. 27,28 Moreover, a study has opined that the adoptive transfer of MDSCs could improve murine pregnancy outcomes. 29 However, relevant research on MDSCs and RSA remains limited.…”
Section: Introductionmentioning
confidence: 99%
“…A heterogeneous population of myeloid cells, termed myeloidderived suppressor cells (MDSC), was described as pathologically differentiated/ activated monocytes and neutrophils [5]. Although initially defined in solid tumors, subsequent discoveries described their roles in different pathological and physiological conditions, including chronic inflammation, sepsis, obesity, aging, and pregnancy (reviewed in [6][7][8][9]). Initially, early studies suggested that nonspecific suppressor cells play a significant role in autoimmunity [10].…”
Section: Introductionmentioning
confidence: 99%